How Good Corporate Governance, Financial Performance and External Factors Influence Company Value - Kurniaty; Yuliastina, Mellani; Nurhayati, Netty; Lesmanawati, Dewi (GOVERNORS, 2024)
The purpose of this study is to examine and explain the effect of good corporate governance on company value, the effect of financial performance on company value, and the influence of external factors on company value. In addition, many previous studies explored good corporate governance using ownership structure indicators, and this study also aims to reexamine the theory that has been used The model used in data analysis in this study is the PLS model by going through four stages of testing, namely individual item reliability, internal consistency reliability, average variance extracted, and discriminant validity. The results of the study show that: 1) Good Corporate Governance has a significant effect on Corporate Value; 2) Financial Performance does not have a significant effect on Company Value; 3) External Factors do not have a significant effect on Company Value. The resulting Termination Test (R2) was 29.3%, meaning that the contribution of the influence of Good Corporate Governance, Financial Performance, and External Factors variables on Company Value was 29.3% including moderate categories, while the remaining 70.7% was influenced by other variables that were not included in this model.